2005
DOI: 10.1016/j.tsf.2005.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Indium Tin Oxide morphology and the performances of polymer light-emitting diodes

Abstract: :This paper reports on performance enhancement of polymer light-emitting diodes (PLEDs) based on poly(2,5-bis(3′,7′-dimethyl-octyloxy)1,4-phenylene-vinylene) (BDMO-PPV) after Indium Tin Oxide (ITO) pre-treatment. Diluted aqua regia surface treatments of ITO substrates were investigated before PLEDs manufacturing. The correlation between ITO surface morphology and the properties of devices were discussed. The residual roughness, the global ITO thickness and developed anodic active area were found extremely depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 25 publications
0
26
2
Order By: Relevance
“…However, they did not observe a major shift in the threshold voltage. The main difference in the surfaceroughness effect between these [24,25] and our present work lies in a large threshold-voltage shift, which may be attributed to the difference of single-layer and double -layer OLEDs.…”
Section: (C) Optical Transmittancecontrasting
confidence: 53%
See 1 more Smart Citation
“…However, they did not observe a major shift in the threshold voltage. The main difference in the surfaceroughness effect between these [24,25] and our present work lies in a large threshold-voltage shift, which may be attributed to the difference of single-layer and double -layer OLEDs.…”
Section: (C) Optical Transmittancecontrasting
confidence: 53%
“…In addition, for ITO deposited in O 2 and at 12 cm, the OLED shows a remarkable improvement with a reduced threshold voltage (-3.7 V), a higher rate of charge injection, a wider operating voltage range (+ 1.7 V) and hence an enhanced maximum brightness (+ 74 %). Wantz et al [24] and Li et al [25] reported that increasing the ITO surface roughness, by diluted aquaregia surface treatment, could greatly enhance their bi-layer OLED brightness although the lifetime was not investigated. They attributed the surface roughness effect to an increase of the anodic contact surface area and unevenness in enhancing the hole injection from the ITO layer into the hole transport layer.…”
Section: (C) Optical Transmittancementioning
confidence: 99%
“…However, they did not observe a major shift in the threshold voltage. The main difference in the surface-roughness effect between these 25,26 and our present work lies in a large threshold-voltage shift, which may be attributed to the difference of single-layer and double-layer OLEDs.…”
Section: (B) Microstructurescontrasting
confidence: 55%
“…higher rate of charge injection, a wider operating voltage range (+1.7 V) and hence an enhanced maximum brightness (+74 %). Wantz et al 25 and Li et al 26 reported that increasing the ITO surface roughness, by diluted aquaregia surface treatment, could greatly enhance their bi-layer OLED brightness although the lifetime was not investigated. They attributed the surface roughness effect to an increase of the anodic contact surface area and unevenness in enhancing the hole injection from the ITO layer into the hole transport layer.…”
Section: (B) Microstructuresmentioning
confidence: 99%
“…It also smoothes the ITO surface and therefore prevents any possible short circuits due to the ITO spikes. [82] The further device elaboration steps and characterizations were carried out under an inert atmosphere (N 2 ) inside a glove box system. Then the emissive layer was spin-coated on top of the PEDOT-PSS layer at 1000 rpm from a xylene solution.…”
mentioning
confidence: 99%